Irrigation in Agroecosystems - Ondrašek, Gabrijel (IntechOpen, 2019)
The agroecosystem is one of the most fascinating, purposely human-created functional units, by which human species made a huge leap from predators and nomads to food growers (agriculturists). Irrigation is one of the oldest and still one of the most effective agricultural practices for providing continuous and quality foodstuffs.